Association between primary origin (head, body and tail) of metastasised pancreatic ductal adenocarcinoma and oncologic outcome: A population-based analysis. (January 2019) - Mackay, Tara M.; van Erning, Felice N.; van der Geest, Lydia G.M.; de Groot, Jan Willem B.; Haj Mohammad, Nadia; Lemmens, Valery E.; van Laarhoven, Hanneke W.; Besselink, Marc G.; Wilmink, Johanna W.; ,
Abstract: Introduction: The relation between the primary origin of metastasised pancreatic ductal adenocarcinoma (PDAC)—head, body or tail—metastatic patterns and outcomes has not yet been investigated in large population-based studies. Methods: Patients with metastasised PDAC at diagnosis from the Netherlands Cancer Registry were included (2005–2015). We compared number of metastatic organ sites (1, 2, ≥3) and specific metastatic organ sites (peritoneum, liver, lung and extra-regional lymph nodes) for the different primary tumour locations. Cox regression analyses were used to determine the association of tumour location and metastatic organ site(s) with overall survival. Results: Overall, we included 9952 patients with metastasised PDAC. The primary origin was head in 5644 (57%), body in 1671 (17%) and tail in 2637 (26%) patients. Differences between primary origins were the number of metastatic organ sites (proportions ≥3 sites for head: 4%, for body: 8% and for tail: 13%, p < 0.0001) and peritoneal metastases (present in 13% for head, 24% for body and 30% for tail; p < 0.0001). Median overall survival was 2.6 months for head PDAC (reference), 2.4 months for body PDAC (HR 1.02 [0.97–1.08]) and 1.9 months for tail PDAC (HR 1.20 [1.15–1.26]). Of patients with one metastatic organ site, the worst survival compared with other sites was seen with liver only metastases (2.5 months vs. 2.7–5.1 months), and the best survival for patients, with extra-regional lymph node only metastases (5.1 months). Conclusion: Metastatic patterns differ among the primary origins for PDAC with metastasised tail tumours having more metastatic sites, more often peritoneal metastases and worse survival. Highlights: In total, 9952 patients with metastasised pancreatic cancer were investigated. Metastatic patterns differ among the primary origins for pancreatic cancer. Metastasised tail cancers have more metastatic sites than the head or body. Metastasised tail cancers have more peritoneal metastases than the head or body. Overall survival was worst for patients with metastasised tail cancer.